Impact of Effective Communication on the Quality of Excellent Service and Patient Satisfaction in the Outpatient Department - Ratna Sari, Dwi; Kartikasari, Dhian; Herya Ulfah, Nurnaningsih (KnE Life Sciences, 2021)
Effective communication is crucial to support nurses in providing excellent service, including a caring attitude towards patients to help facilitate their needs and to realize patient satisfaction. The purpose of this literature review was to describe the impact of effective communication on the improvement of the quality of excellent service and patient satisfaction in outpatient departments. This review was conducted by searching published articles on Google with selected keywords including “effective communication,” “excellent service” and “patient satisfaction.” The search was limited to publications between 2009 and 2019. The result of the study showed that effective communication can significantly impact the improvement of excellent service quality, thereby increasing patient satisfaction with the health care they receive. The study recommends a collaboration between the HR and the Head of Nursing to conduct effective communication training. Nurses are expected to be able to improve their effective communication skills with patients, and further studies are needed to dig deeper into the impact of effective communication on improving the quality of excellent service and patient satisfaction. Keywords: effective communication, excellent service patient satisfaction